2022
DOI: 10.1093/brain/awac114
|View full text |Cite
|
Sign up to set email alerts
|

Human lesions and animal studies link the claustrum to perception, salience, sleep and pain

Abstract: The claustrum is the most densely interconnected region in the human brain. Despite the accumulating data from clinical and experimental studies, the functional role of the claustrum remains unknown. Here, we systematically review claustrum lesion studies and discuss their functional implications. Claustral lesions are associated with an array of signs and symptoms, including changes in cognitive, perceptual and motor abilities; electrical activity; mental state; and sleep. The wide range of symptoms observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 170 publications
(178 reference statements)
5
36
0
Order By: Relevance
“…The profile of RSP projecting cells through development we report here is consistent with the tight cluster of cells observed in the claustrum in the adult (Zingg et al 2018;Marriott et al 2021;Shelton et al 2022). We find no projections to RSP from insula and other claustrum adjacent structures even in the youngest brains.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The profile of RSP projecting cells through development we report here is consistent with the tight cluster of cells observed in the claustrum in the adult (Zingg et al 2018;Marriott et al 2021;Shelton et al 2022). We find no projections to RSP from insula and other claustrum adjacent structures even in the youngest brains.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, we specifically investigated when claustrum axons first connect to two distinct ipsilateral target regions: anterior cingulate and retrosplenial cortex. RSP projections were chosen, because they are widely used in adult brains as a means to access claustrum cells for genetic manipulation via retrograde viral transfection including in species other than mouse (Zingg et al 2018;Dillingham et al 2019;Shelton et al 2022), and ACA because of its reported dense innervation by claustrum (Wang et al 2017;White et al 2018;Zingg et al 2018;Chia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations